Evaluation of the 3rd semester reading syllabus for English major students at Hanoi University of Industry (HaUI). M.A Thesis Linguistics - Nguyễn, Thu Hương (ĐHNN, 2017)
First , the study found both the strengths and weaknesses of the reading syllabus which was implemented for at least two courses . Second, it proposes clearer goals and objectives which help student understand what they need to do to obtain the objectives and goals. This study lays the foundation for other evaluation studies at the English Department at HaUI .